Identification of blast-resistance loci through genome-wide association analysis in foxtail millet (Setaria italica (L.) Beauv.) - Zhi-jiang LI; Guan-qing JIA; Xiang-yu LI; Yi-chu LI; Hui ZHI; Sha TANG; Jin-feng MA; Shuo ZHANG; Yan-dong LI; Zhong-lin SHANG; Xian-min DIAO (Journal of Integrative Agriculture, 2021)
Blast disease caused by the fungus Magnaporthe grisea results in significant yield losses of cereal crops across the world. To date, very few regulatory genes contributing to blast resistance in grass species have been identified and the genetic basis of blast resistance in cereals remains elusive. Here, a core collection of foxtail millet (Setaria italica) containing 888 accessions was evaluated through inoculation with the blast strain HN-1 and a genome-wide association study (GWAS) was performed to detect regulators responsible for blast disease resistance in foxtail millet. The phenotypic variation of foxtail millet accessions inoculated with the blast strain HN-1 indicated that less than 1.60% of the samples were highly resistant, 35.25% were moderately resistant, 57.09% were moderately susceptible, and 6.08% were highly susceptible. The geographical pattern of blast-resistant samples revealed that a high proportion of resistant accessions were located in lower latitude regions where the foxtail millet growing season has higher rain precipitation. Using 720000 SNP markers covering the Setaria genome, GWAS showed that two genomic loci from chromosomes 2 and 9 were significantly associated with blast disease resistance in foxtail millet. Finally, eight putative genes were identified using rice blast-related transcriptomic data. The results of this work lay a foundation for the foxtail millet blast resistance biology and provide guidance for breeding practices in this promising crop species and other cereals.